Coping strategies and the quality of life of call center agents on graveyard shift - Bituin, Rainier Joseph R. (2013.)
The study aimed to examine relationships between the coping strategies and the Quality of Life (QOL) of Filipino call center agents on graveyard shift. The study also determined specific coping strategies utilized by the call center agents and related demographic and job variables. -- Findings from previous studies determined that coping strategies could influence quality of life and that the two concepts were related. However, these were done abroad whose populations, generally were patients with various medical ailments. There is little knowledge on how coping strategies would affect quality of life on a supposedly well sample like the call center agents. The study intends to fill the information gap of coping strategies and quality of life studies in the Philippines as there have been no studies from the viewpoint of health professions, notably from nursing or medicine. -- The study was guided by Sister Callista Roy's Adaptation Model to explore coping with the concept of man as an adaptive system wherein outputs or behavioural responses referred to as coping mechanisms to respond to environment stimuli. The utilization of the coping strategies based on the needs of that person would have been reflected in the physiological beaviour of the person, in order to maintain a degree of wholeness achieved through proper adaptation. -- A quantitative, non-experimental, descriptive correlational research design was used to examine the relationship between the variables. Conducted from August to December 2012, a total of 175 call center agents from 3 sites in Metro Manila were purposively recruited and participated. Research instruments used were: Demographic Data and Job Information Checklist to determine the demographic and job related variables; Jalowiec Coping Scale (JCS) which measured coping and the World Health Organization Quality of Life-BREF instruments to determine quality of life. -- Findings of the study revealed that optimistic, self reliant, confrontive and supportive coping based on the JCS were the most frequently utilized. The least used were evasive, fatalistic, palliative and emotive coping. In general, problem focused coping was found to be used more than the emotion focused or affective type of coping. Selected demographic and job related factors correlated with coping are: Age which was positively correlated with problem focused coping while social support and monthly income which both had weak negative correlation with emotion focused coping. -- Problem focused coping was significantly correlated to over-all quality of life and the social and environment domains. Emotion focused coping, meanwhile was negatively correlated to over-all QOL and the psychological and environmental domains. Both 2 general types of coping, though had weak correlations with QOL. -- Strengthening good coping strategies, particularly problem focused and lessened use of the negative ones can have an impact, or help improve quality of life. The nurse, together with the human resource personnel of the respective call centers, concerned with the response of individual to their health states should serve as patient advocates and use health promotion as guide in helping the call center agents cope to have a better quality of life.
Thesis (Master of Arts in Nursing - Adult Health Nursing) -- University of the Philippines Manila, May 2013.
Bibliography: leaves 138-147.
Keywords: Call center agents -- Quality of life